THE RELATIONSHIP BETWEEN CELEBRITY WORSHIP AND THE SELF-CONCEPT OF K-POP FAN COLLEGE STUDENTS IN BANDUNG - Rachmawati Rachmawati; Rina Nurhudi Ramdhani (Universitas Pendidikan Indonesia, 2024)
This study aims to explore the relationship between celebrity worship and self-concept among K-pop fan college students in Bandung by utilizing a mixed-methods approach, including case studies, quantitative surveys, and in-depth interviews. The findings reveal that the attachment of K-pop fans to their idols affects their self-perception, influencing aspects from physical appearance to personal values. Results indicate that while celebrity worship exists at a moderate level, the impact of idols on young adult students fosters positive motivation and self-confidence, without leading to obsessive behavior. This research highlights that admiration for popular culture can contribute to identity formation and enhance self-concept.